The Role of International Organizations in Maintaining Environmental Security - Volik, Viacheslav; Bespalova, Olha (Teisė, 2021)
The conducted research aims to determine the role of international organizations in the field of maintaining environmental safety. It is concluded that the relevance of the activities of international environmental organizations, governmental and non-governmental, both individually and collectively, make an important contribution to the processes of ensuring and maintaining environmental safety throughout the world, showing the need to disseminate environmental education, invest in environmental projects, increase society’s involvement in cooperation at the national and international levels, update scientific theoretical and practical research, and preserve natural heritage for future generations.
Keywords: environmental security; nternational environmental organization; environmental policy; international security; national security; environmental problems